Educational Development in Egypt And Turkey: Abduh’s Integration Versus Ataturk’s Unification - Rahimah, Embong; Ahmad Bazli, Shafie; Mohd Taufiq, Abd. Talib; Abdul Hakim, Abdullah; Fadzli, Adam (2015)
This article provides a historical review on the educational developments in the Muslim world particularly in Egypt and Turkey. Both countries are taken into consideration in an attempt to find out realistic means of integrating and synthesizing two dissimilar education systems formed by „Abduh‟s „integration‟ and Ataturk‟s „unification‟. Subsequently, it analyzes the significant impacts of colonialism and modernization processes upon the existence of dual systems of education in the Muslim world. In the late eighteenth century, most of the Muslim countries were under Western colonialism. Apparently, these countries began to gain political independence about the mid of nineteenth century with the exception of Turkey. It is found that Western colonialism in the nineteenth and twentieth centuries have actually brought a revolutionary shift including educational change. It was in contrast to the conquest by the Mongols in the thirteenth century, which was military in nature, which brought a whole destruction of Muslim world politically and intellectually. Hence, it is significant to analyze the effort of „integration‟ initiated by „Abduh and „unification‟ introduced by Ataturk. „Abduh promoted educational reform with the aims of removing the dichotomy between the existing education systems and of creating an integrated system of education. On the other hand, Ataturk attempted at unifying, instead of integrating the educational systems. In the name of unification, many modern scientific, technological and professional schools and institutions were established in Turkey. As a result, the religion was divorced from the modern education. This writing focuses on qualitative method by using content analysis approach on issues related to comparative educational development formed by both reformers. The promoted comparative approaches inevitably avail ideas for integrated curriculum for Muslim education in this contemporary world